Self-referencing surface plasmon sensor for resolution enhancement - Reza Kohandani; Simarjeet Saini (Scientific Reports)
Abstract In this paper, a self-referencing evanescent field sensor based on surface plasmon resonances is designed and fabricated. The sensor is based on sub-wavelength two-dimensional gold gratings and is optimized to detect changes in the surrounding refractive index for a water-like material. The sensor has a dedicated mode for self-referencing, which is isolated from the surrounding environment and can be used to correct errors due to temperature variations. To understand the important design parameters and optimize the sensor for best performance, many variations were fabricated and measured experimentally. Using a localized surface plasmon resonance dominant mode, a high sensitivity of 435 nm/RIU was achieved experimentally, while the self-referencing mode was successfully isolated from the surrounding environment within a refractive index range of 1.34 to 1.39. Further, we show that by incorporating the self-referencing mode into the sensitivity measurements, the resolution of the sensor can be improved by a factor of 3.6. This approach can be employed effectively for resolution enhancement of the plasmonic sensors in the presence of environmental variations.